Avoiding the Subject Media, Culture and the Object - Clemens, Justin (Amsterdam University Press, 2004)
What can Roger Rabbit tell us about the Second Gulf War? What can a woman married to the Berlin Wall tell us about posthumanism and inter-subjectivity? What can DJ Shadow tell us about the end of history? What can our local bus route tell us about the fortification of the West? What can Reality TV tell us about the crisis of contemporary community? And what can unauthorized pictures of Osama Bin Laden tell us about new methods of popular propaganda? These are only some of the thought-provoking questions raised in this lively and erudite collection of inter-related essays on the postmillennial mediascape. Students and teachers of visual culture, critical theory, cultural studies, film theory, and new media, will find a wealth of ideas and insights in this fresh approach to the electronic environment. Avoiding the Subject argues for a new sensitivity and empathy towards objects (including, and especially, human objects - such as refugees, "enemy combatants," collateral damage, etc.). Whether the focus be on the specifically postcolonial trauma of Australian detention centers, or the viral mutations of propaganda in the age of the internet, each chapter attempts to "avoid the subject" in order to escape the egocentric confines of our own subjective perspectives.